Annual Plan 1971-72, Statistical Statements Planning Department - Planning Commission (Planning Commission, 1971)
Agricultural Production, Agricultural Research and Education, Minor Irrigation, Soil Conservation, Ayacut Development Programme, Animal Husbandry, Dairying and Milk Supply, Forests, Fisheries, Warehousing and Marketing, Co-operation, Community Development, Panchayats, Multipurpose Projects, Major and Medium Irrigation, Anti-waterlogging, Drainage and Flood Control, Power Projects, Industries.
Statistical Statements Planning Department Punjab